Physical and physiological quality of seeds of Ricinus communis L. after the debarking - França, Pablo Radamés Cabral de; Almeida, Francisco de Assis Cardoso; Silva, Odilon Reny Ribeiro Ferreira da; Jerônimo, Jeane Ferreira (Comunicata Scientiae, 2013)
The production of high quality seeds of Ricinus communis, is a major challenge for agricultural research, need to adopt technologies for evaluating the physical and physiological quality of seeds, especially during processing. The objective of this study was to evaluate the germination and vigor of seeds of R. communis BRS Energy and the damage caused by types of processing. After processing by methods manual, batting, machine of crank and prototype, the seeds were conducted at the Laboratory of Storage and Processing of Agricultural Products of UFCG and subjected to tests of germination, vigor (first count, germination speed index, length of root and shoot, and dry weight of root and shoot) and tetrazolium. We used a completely randomized design with four treatments and five replicates of 50 seeds. The peeling performed manually and by mean of the prototype allowed positive results for germination and vigor (90% for both tests) as well as in tetrazolium test in which they were checked low percentages of damage (8.8 and 9.6 %, respectively). Peeling done by machine activated by the crank provided results that interfered vigor of seeds, mainly in length and dry weight of seedling. While the method of batting promoted lower germination percentage (64%) and a higher percentage of damage (23.2%), mainly affecting the hypocotyl-radicle axis. The processing performed manually and by means of prototype does not affect the germination and vigor of seeds, although the latter is considered more economically advantageous for the processing of R. communis; whereas the method of the batting is considered unfeasible for this stage of production due to the high percentage of seeds with damage, especially in the region of hypocotyls-radicle axis of the seeds.